STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KUANTITAS PESERTA DIDIK BARU DI SMK SALAFIAH KEJAYAN PASURUAN - Muawanah, Arofatul; Islamiyah, Sheilatul (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
The purpose of this research is to map out what strategies are applied at SMK Salafiah Kejayan Pasuruan. This is very reasonable, because in fact SMK Salafiah Kejayan is a newly established institution, namely since 2015. However, every year this institution is able to get quite a lot of students. For example, in the 2020/2021 school year there are 172 registered students and in the 2021/2022 school year there are 207 with details of 125 male and 82 female students.The research method used is qualitative by using data collection techniques in the form of observation and interviews.The results of this study indicate that the strategy used by SMK Salafiah Kejayan Pasuruan in increasing the number of new students is to use a promotion mix consisting of advertising, personal selling, sales promotion, public relations, direct marketing and word of mouth. For advertising, apply online advertising and offline advertising; personal selling is applied by assigning a board of teachers and students to participate in socialization activities at the targeted school; sales promotions by providing discounts for the first registrants and scholarships for outstanding students and poor families; public relations still found one research that discusses SMK Salafiah Kejayan, namely the use of the Form To method in PAI learning; direct marketing by scheduling direct meetings between the Salafiah Kejayan Vocational School and the target schools; and for word of mouth by establishing good communication and friendly behavior to the general public and routinely conducting social activities aimed at the surrounding community